FOXF1 Mediates Endothelial Progenitor Functions and Regulates Vascular Sprouting - Sturtzel, Caterina; Lipnik, Karoline; Hofer-Warbinek, Renate; Testori, Julia; Ebner, Bettina; Seigner, Jaqueline; Qiu, Ping; Bilban, Martin; Jandrositz, Anita; Preisegger, Karl-Heinz; Untergasser, Gerold; Gunsilius, Eberhard; et al. (Frontiers in Bioengineering and Biotechnology, 2018)
Endothelial colony forming cells (ECFC) or late blood outgrowth endothelial cells (BOEC) have been proposed to contribute to neovascularization in humans. Exploring genes characteristic for the progenitor status of ECFC we have identified the forkhead box transcription factor FOXF1 to be selectively expressed in ECFC compared to mature endothelial cells isolated from the vessel wall. Analyzing the role of FOXF1 by gain- and loss-of-function studies we detected a strong impact of FOXF1 expression on the particularly high sprouting capabilities of endothelial progenitors. This apparently relates to the regulation of expression of several surface receptors. First, FOXF1 overexpression specifically induces the expression of Notch2 receptors and induces sprouting. Vice versa, knock-down of FOXF1 and Notch2 reduces sprouting. In addition, FOXF1 augments the expression of VEGF receptor-2 and of the arterial marker ephrin B2, whereas it downmodulates the venous marker EphB4. In line with these findings on human endothelial progenitors, we further show that knockdown of FOXF1 in the zebrafish model alters, during embryonic development, the regular formation of vasculature by sprouting. Hence, these findings support a crucial role of FOXF1 for endothelial progenitors and connected vascular sprouting as it may be relevant for tissue neovascularization. It further implicates Notch2 , VEGF receptor-2 and ephrin B2 as downstream mediators of FOXF1 functions.